Who Runs the AEA? - Hoover, Kevin D.; Svorenčík, Andrej (Journal of Economic Literature, 2023)
The leadership structure of the American Economic Association is documented using a biographical database covering every officer and losing candidate for AEA offices from 1950 to 2019. The analysis focuses on institutional affiliations by education and employment. The structure is strongly hierarchical. A few institutions dominate the leadership, and their dominance has become markedly stronger over time. Broadly two types of explanations are explored: that institutional dominance is based on academic merit or that it is based on self-perpetuating privilege. Network effects that might explain the dynamic of increasing concentration are also investigated. (JEL A11, B29, B30, Z13)